Developing Red-White Monopoly Games through Integrative Thematic Learning in the Primary School - Nilam Sri Anggraheni; Nurul Hidayah; Ayu Nur Shawmi (UIN Siber Syekh Nurjati Cirebon, 2019)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â AbstractPlaying is a fun activity and liked by children. It can be used as a media of learning. The observations carried out in SD Negeri 3 Sawah Lama Bandar Lampung found that the learning media used was not interesting for students to learn. The aims of the study are to determine the steps in developing a game of red-and-white monopoly media;to know the quality of red-and-white monopoly games; and to find out the responses of students to the red-and-white monopoly game. This study is a research anddevelopment (R & D) using the Borg and Gall model. The steps start from exploring potential aspect and its problems, data collection, product design, design validation, design revision, product testing, and product revision. The techniques of data collection are observations, interviews, and questionnaires.The data analysis technique uses is qualitative descriptive. The results of the analysis show that the assessment of material experts gained an average of 93%